2018
DOI: 10.3389/fphys.2018.00137
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin Affects the Growth of Spodoptera litura Fabricius by Inducing Apoptosis in Larval Midgut

Abstract: Azadirachtin, the environmentally friendly botanical pesticide, has been used as an antifeedant and pest growth regulator in integrated pest management for decades. It has shown strong biological activity against Spodoptera litura, but the mechanism of toxicity remains unclear. The present study showed that azadirachtin inhibited the growth of S. litura larvae, which was resulted by structure destroy and size inhibition of the midgut. Digital gene expression (DGE) analysis of midgut suggested that azadirachtin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 65 publications
3
25
0
5
Order By: Relevance
“…This property adversely affects the ecdysteroid and juvenile hormones thus preventing pest proliferation. Moreover, Shu et al (2018) reported that azadirachtin inhibited the growth of Spodoptera litura larvae by inducing apoptosis and destroying the structure of the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…This property adversely affects the ecdysteroid and juvenile hormones thus preventing pest proliferation. Moreover, Shu et al (2018) reported that azadirachtin inhibited the growth of Spodoptera litura larvae by inducing apoptosis and destroying the structure of the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial and cytosolic proteins were isolated by mitochondrial protein extraction kit (KeyGEN, Nanjing, China) according to manufacturer's protocol. Western blot analysis for caspase‐3 (Cell signaling technology) and cytochrome C (CYC, Beyotime Biotechnology) were carried out according to our previously described in this paper . DNA fragmentation in the testis of S. litura was detected using the principle of TdT‐mediated dUTP nick‐end labeling (TUNEL), a marker of apoptosis .…”
Section: Methodsmentioning
confidence: 99%
“…The transcript levels of Bm-IBM1 in BmN cells and pupae of Bombyx mori were up-regulated after infection by baculovirus B. mori Nucleopolyhedrovirus [13]. Sl-IBM1 was induced by azadirachtin along with increased apoptosis in the midgut of Spodoptera litura [29]. In this study, we demonstrated that azadirachtin, camptothecin, and UV induced expression of Sf-IBM1 in Sf9 cells along with increased apoptosis.…”
Section: Discussionmentioning
confidence: 55%
“…The Caspase-3 activity assay was measured using a Caspase-3 Colorimetric Assay Kit (KeyGEN BioTECH, Nanjing, China) as previously described [29]. Cells under different treatments were collected by centrifugation and washed with PBS for two times.…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%